India : Revitalizing Punjab's Agriculture - World Bank (Washington, DC, 2013)
Punjab has played a pioneering role in Indian agriculture. Three key challenges face Punjab agriculture - restoring growth, promoting sustainable use of natural resources, and rationalizing fiscal outlays on the sector. The main content of this paper includes: development and outcomes; policies, public expenditures and provision of public services; and options and recommendations. The options and recommendations include: enterprise options for growth and diversification; conceptual matrix for analyzing policy and institutional options; reforming price policy and public expenditures; and institutional reform characterized by revamping agricultural research and extension, regulation and reform of canal irrigation and groundwater management policies, reforming the marketing system, and contract farming.